Penyuluhan Cara Merawat Anggota Keluarga dengan Perilaku Kekerasan di Banda Gadang Kota Padang - Miswarti Miswarti; Metha kemala Rahayu; Maidawilis Maidawilis (Universitas Kristen Indonesia Toraja, 2024)
The aim of this community service activity is to provide health education in the form of counseling on how to care for mental disorders patients with problems at risk of violent behavior in Banda Gadang, Padang City. The method of implementing community service activities includes three stages of activity, namely preparation for implementation, preparation for completeness and implementation of health education. The number of participants who attended was 16 people. The activity was held in Banda Gadang, Padang city. The target of this outreach activity is the community, including parents and closest family. Based on the results of the health education carried out, the results show that there is an increase in the family's ability to understand violent behavior by 15%, the causes of violent behavior by 15%, signs and symptoms of violent behavior by 10%, the consequences of violent behavior by 15% and family efforts in caring for family members with violent behavior. by 20%. Health education activities went well and received a positive response from the community and nurses. There was an increase in knowledge by all participants present. This is a real form of cooperation between educational and health institutions as well as a form of service to the community as one part of the Tri Dharma of Higher Education.